Pengembangan Ruang Budi Daya Peternakan Kelinci di Desa Margamukti Sumedang Untuk Mendukung Perekonomian Desa Berkelanjutan - Hilwati Hindersah; Atih Rohaeti Dariah; A. Harits Nu’man; Rose Fatmadewi; Neng Dewi Himayasari; Nadya Safitri (UNISBA Press, 2024)
Abstract. Margamukti Village, located in North Sumedang Sub-district, Sumedang Regency, has great potential for the development of rabbit farming as an effort to improve the village economy. This study aims to understand community perceptions and support for the development of rabbit farming spaces. This research applied a mixed method which included a comprehensive literature review as well as secondary data collection, field documentation and Focus Group Discussion (FGD). The results of the research include that the rabbit farming area in Margamukti Village is included in the cultivation area/zone, precisely the agricultural zone. For rabbit livestock-based economic development, alternative solutions with agritourism-based economic development. Develop agritourism by utilizing natural beauty or local agricultural potential. This could include organic farming tours or urban farming activities integrated with rabbit farming. It is important to conduct a market analysis prior to sustainable village economic development steps. The farmers of Margamukti Village should form a community such as a cooperative specifically for rabbit farming. Abstrak. Desa Margamukti, yang terletak di Kecamatan Sumedang Utara, Kabupaten Sumedang, memiliki potensi besar untuk pengembangan budi daya kelinci sebagai salah satu upaya meningkatkan perekonomian desa. Penelitian ini bertujuan untuk memahami persepsi dan dukungan masyarakat terhadap pengembangan ruang budidaya peternakan kelinci. Penelitian ini menerapkan metode campuran (mixed method) yang meliputi tinjauan literatur komprehensif serta pengumpulan data sekunder, dokumentasi lapangan dan Focus Group Discussion (FGD). Hasil penelitian antara lain, area peternakan kelinci di Desa Margamukti termasuk ke dalam kawasan/zona budidaya, tepatnya zona pertanian. Untuk pengembangan ekonomi berbasis ternak kelinci, solusi alternatif dengan pengembangan ekonomi berbasis agrowisata. Mengembangkan agrowisata dengan memanfaatkan keindahan alam atau potensi pertanian setempat. Ini dapat mencakup wisata pertanian organik atau kegiatan urban farming yang terintegrasi dengan peternakan kelinci. Penting dilakukan analisis pasar sebelum langkah pengembangan ekonomi desa yang berkelanjutan. Para peternak Desa Margamukti sebaiknya membentuk komunitas semacam koperasi khusus untuk usaha ternak kelinci.